DAMPAK PERALIHAN KEWENANGAN PEMERINTAH DALAM KONSERVASI SUMBER DAYA LAUT DI KOTA PARIAMAN TAHUN 2017-2022 - Putri, Suci Ananda; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
With the enactment of Law No. 23 of 2014 concerning Regional Government, the authority to manage Regional Marine Protected Areas located in Regencies/Cities is now the authority of the Provincial Government. This policy change has an impact on Turtle Conservation in Pariaman City. This study discusses the Impact of the Transfer of Government Authority on Marine Resources Conservation Management Institutions in Kota Pariaman in 2017-2022 and discusses the Impact of the Transfer of Government Authority in Marine Resource Conservation in Pariaman City in 2017-2022. The research method used is descriptive with a qualitative approach. The data collected in this study through interviews, observation, and documentation. The results of the study explain the impact of the Transfer of Government Authority in Marine Resources Conservation Management Institutions in Pariaman City in 2017-2022 has an impact on several aspects. (1) Inadequate human resources, decreased management of UPTD Conservation in saving turtle eggs, insufficient budget, organizational structure that changed from City Government to Provincial Government and conservation assets that have been damaged a lot. (2) The impact of the Transition of Government Authority in the Conservation of Marine Resources for 2017-2022 also has an impact outside the UPT Conservation Institution, namely, Improvement of the community's economy, Policy changes, government support, conservation environmental quality has unique power, Increase in salaries earned by contract workers at UPTD held by the Provincial Government, Environmental conservation area which is used as road access for the community, UPTD KPSDKP forms a service to support and carry out conservation activities, Community participation in preserving turtle conservation, and Turtle Conservation which is used as an ecotourism area and also education. Keywords: Impact, Transfer of Authority, Conservation, Marine Resource